59 Collagenase Clostridium Histolyticum Treatment for Peyronie's Disease: Analysis of Outcomes and Cumulative Benefits After Each Injection Cycle. Issue 1 (1st April 2022) - Ziegelmann, M; Liu, G; McLane, M; Hu, Y; Trost, L
ABSTRACT: Introduction: The efficacy and safety of collagenase clostridium histolyticum (CCH) for the treatment of Peyronie's disease (PD) were demonstrated in two phase 3, randomized, double-blind, placebo-controlled studies. CCH injections were administered in up to 4 treatment cycles at 6-week intervals; each cycle included two injections 1-3 days apart. Objective: To evaluate incremental changes in penile curvature over the course of CCH treatment in men with PD. Methods: A post hoc analysis was conducted using pooled data from the 2 placebo-controlled trials. Change from baseline and from the previous penile curvature measurement were calculated after each of the 4 treatment cycles (Weeks 6, 12, 18, and 24). For all patients, treatment included penile plaque modeling. For CCH vs placebo, mean percentage change in penile curvature was compared using a two-sample t-test; percentage of patients classified as treatment responders (defined as curvature reduction ≥20%) was compared using Fisher's exact test. Results: The population included 832 adult men (CCH [n=551]; placebo [n=281]) who received ≥1 injection of study medication. At baseline, mean ± standard deviation (SD) penile curvature was 50.6±14.7 degrees in the CCH group and 50.4±14.1 degrees in the placebo group. Compared with baseline, the mean ± SD percentage change in penile curvature was -12.8±20.3% for CCH vs -6.2±18.8% for placebo after the first treatment cycle, -22.6±23.5% vs -10.6±23.1% after the second, -29.9±25.0% vs -14.6±24.0% after the third, and -33.1±28.0% vs -16.6±25.5% after the fourth (all P<0.001 vs placebo; Figure 1A). Comparing change from the previous measurement (ie, incremental change from previous treatment cycle [eg, between first and second; second and third, etc]), mean ± SD percentage reduction in penile curvature was 11.1±21.8% vs 5.0±16.4% after the second treatment cycle (P<0.001 vs placebo), 9.6±21.8% vs 3.9±17.0% after the third (P<0.001) and 6.3±23.0% vs 2.0±17.2% after the fourth (P=0.009; Figure 1B). The percentage of patients with ≥20% reduction in penile curvature since the previous measurement (cycle) was 29.9% for CCH group vs 18.3% for the placebo group after the first treatment cycle (P=0.0003), 29.1% vs 16.9% after the second (P=0.0002), 25.2% vs 12.8% after the third (P<0.0001), and 20.2% vs 10.9% after the fourth (P=0.001). For patients with a response after 2 treatment cycles (CCH [n=219]; placebo [n=77]), 40.2% of the CCH-treated patients vs 19.5% of the placebo-treated patients had an additional reduction of ≥20% after completing 4 treatment cycles (P=0.001). In patients with <20% reduction after the initial 2 treatment cycles (CCH [n=205]; placebo [n=168]), 29.8% of patients in the CCH group were classified as treatment responders after completing the fourth injection cycle (versus 20.8% of placebo-treated patients; P=0.057). Conclusions: Data support that incremental benefits were obtained from each of the 4 CCH treatment cycles administered to men with Peyronie's disease. Results would suggest benefits with performing a full series of 4 CCH injections, even among men who are initial non-responders. Disclosure: Yes, this is sponsored by industry/sponsor: Endo Pharmaceuticals Inc. Clarification: Industry initiated, executed and funded study Any of the authors act as a consultant, employee or shareholder of an industry for: Endo Pharmaceuticals Inc.